2017
DOI: 10.1039/c7sm00316a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of hard spheres in a cylinder: a computational and experimental study

Abstract: Hard spheres are an important benchmark of our understanding of natural and synthetic systems. In this work, colloidal experiments and Monte Carlo simulations examine the equilibrium and out-of-equilibrium assembly of hard spheres of diameter σ within cylinders of diameter σ≤D≤ 2.82σ. Although phase transitions formally do not exist in such systems, marked structural crossovers can nonetheless be observed. Over this range of D, we find in simulations that structural crossovers echo the structural changes in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 68 publications
(94 reference statements)
5
36
1
Order By: Relevance
“…The latter clearly shows complex oscillation behaviour which increases the uncertainty of estimate of ξ∆x. [38]. The system is gas-like at P * x = 5, displays zig-zag order at P * x = 25, and exhibits significant helicity at P * x = 45. with the onset of helicity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The latter clearly shows complex oscillation behaviour which increases the uncertainty of estimate of ξ∆x. [38]. The system is gas-like at P * x = 5, displays zig-zag order at P * x = 25, and exhibits significant helicity at P * x = 45. with the onset of helicity.…”
Section: Discussionmentioning
confidence: 96%
“…Once the correlation function has been computed, ξ y can also be obtained by fitting ln g y (|i, j|) = −|i − j|/ξ y + constant. The above numerical approach was first validated by successfully comparing the resulting equation of state with those of previous simulations [34,38] (not shown). We also compared the NN and the NNN calculations of ξ y in 2D and ξ r in 3D systems with each other and with previous results [40].…”
Section: Ii4 Numerical Solutionmentioning
confidence: 99%
“…Considering that our original study of hard-sphere arrangements in a cylinder was motivated as a packing problem [14], it may have seemed plausible that the structures described above would only be of importance close to the incompressible athermal limit. Recently, however, these original findings have been found to be relevant in the self-assembly of hard spheres in cylindrical channels [30]. Remarkably, it is found that at finite temperature and pressure, both uniform and line-slip arrangements can be observed: a steadily increasing pressure can induce transitions between structures, while at a high compression rate some arrangements are found to be dynamically inaccessible [30]; these results are illustrated in terms of a phase diagram that bears a resemblance to the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both natural proteins 3-8 and synthetic colloids [18][19][20][21][22][23][24][25][26][27][28][29] have been shown to readily assemble into symmetric, higher order structures, we anticipate that our SuPrA strategy can now be generalized to create synthetic, scalable…”
Section: 31mentioning
confidence: 99%
“…Notably, while some GFP variants, including the parent protein originally found in Aeqorea Victoria dimerize, the native dimer structure fits poorly into the electron density maps of the protomer, suggesting that the architecture of the protomer is completely novel. 54 The formation of SuPrA protomers appears to be largely independent of the placement of charges, suggesting that oppositely supercharging protein variants may generally drive formation into 'stacked' or brick-like structures whose overall form is determined by symmetric interactions.Given that both natural proteins 3-8 and synthetic colloids [18][19][20][21][22][23][24][25][26][27][28][29] have been shown to readily assemble into symmetric, higher order structures, we anticipate that our SuPrA strategy can now be generalized to create synthetic, scalableAll rights reserved. No reuse allowed without permission.…”
mentioning
confidence: 99%